2018
DOI: 10.1200/jgo.18.00120
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics, Early Outcomes, and Implementation Lessons of Cervical Cancer Treatment Services in Rural Rwanda

Abstract: Purpose Low- and middle-income countries account for 86% of all cervical cancer cases and 88% of cervical cancer mortality globally. Successful management of cervical cancer requires resources that are scarce in sub-Saharan Africa, especially in rural settings. Here, we describe the early clinical outcomes and implementation lessons learned from the Rwanda Ministry of Health’s first national cancer referral center, the Butaro Cancer Center of Excellence (BCCOE). We hypothesize that those patients presenting at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
0
14
2
Order By: Relevance
“…A survey from rural Rwanda reported that 80% of the patients with cervical cancer at the Butaro Cancer Center of Excellence (BCCOE) who were referred to UCI for chemoradiation (there is no available radiation in Rwanda) were able to access treatment. 30 This high proportion of treatment initiation contrasts our findings that women were generally unable to access out-of-country radiation. As expected, in our study, women with locally advanced disease (stage IIB–IIIB) were less likely to be recommended for standard-of-care chemoradiation when there was no available incountry radiation.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…A survey from rural Rwanda reported that 80% of the patients with cervical cancer at the Butaro Cancer Center of Excellence (BCCOE) who were referred to UCI for chemoradiation (there is no available radiation in Rwanda) were able to access treatment. 30 This high proportion of treatment initiation contrasts our findings that women were generally unable to access out-of-country radiation. As expected, in our study, women with locally advanced disease (stage IIB–IIIB) were less likely to be recommended for standard-of-care chemoradiation when there was no available incountry radiation.…”
Section: Discussioncontrasting
confidence: 77%
“…The proportion of participants presenting at late stage (IIB–IVB), 76%, is similar to 20-year-old estimates from the Kampala Cancer Registry, 6 as well as to more recent regional estimates from Northern Uganda, 5 Ghana 29 and Rwanda. 30 Given the lack of national screening and nascent human papillomavirus vaccination efforts, it is unsurprising that the proportion of late-stage disease is unchanged over the last two decades in Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who were in palliative care at BCCOE as their type of treatment were more likely to be LTFU compared to patients who were receiving curative chemoradiation. In our setting, palliative care services are provided at BCCOE, but most of these patients receive these services at their local district hospitals, closer to their home to reduce the burden of travelling [ 16 ]. Information sharing between facilities may be imperfect, and thus transfers of patients for palliative care may appear as LTFU in BCCOE records.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are asked to return every three months for the first year, every six months for the second year and once per year thereafter. Further details about cervical cancer treatment at BCCOE can be found in Park et al, 2018 [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The proportion of participants presenting at late stage (IIB-IVB), 76%, is similar to 20 year-old estimates from the Kamala Cancer Registry, 6 as well as to more recent regional estimates from Northern Uganda, 5 Ghana, 27 and Rwanda. 28 Given the lack of national screening and nascent HPV vaccination efforts, it is unsurprising that the proportion of late stage disease is unchanged over the last two decades in Uganda.…”
Section: Discussionmentioning
confidence: 99%